Analisis Penerapan Metode Wafa Dalam Meningkatkan Kemampuan Hafalan Surat Pendek Anak Usia 5–6 Tahun. - Swandra Rahayu; Nelti Rizka; Elsa Fitriyani (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2026)
The ability to memorize short surahs is an important aspect in developing religious and moral values in early childhood education. Early exposure to Qur'anic memorization can stimulate cognitive development, memory, and spiritual awareness in children. However, many children experience difficulties in memorizing Qur'anic verses due to the lack of appropriate learning methods. One method that can support memorization activities is the Wafa method, which emphasizes rhythm, repetition, and engaging learning approaches suitable for early childhood. This study aims to analyze the implementation of the Wafa method in improving the ability of children aged 5–6 years to memorize short surahs at TK Bina Insani Dumai. This research uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving teachers and children in the learning process. The data were analyzed using the Miles and Huberman model which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the application of the Wafa method can improve children's ability to memorize short surahs. The improvement is seen from children's ability to repeat verses, follow the rhythm of recitation, and memorize surahs more easily and enthusiastically. The learning process becomes more interactive because the method integrates rhythm, gestures, repetition, and storytelling. Therefore, the Wafa method can be used as an effective learning strategy in improving Qur'anic memorization ability in early childhood education